1992
DOI: 10.1177/1059601192172003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between an Organization's Actual Human Resource Efforts and Employee Attitudes

Abstract: Personnel management theorists and practitioners have assumed that human resource activities have a positive effect on employee attitudes. The present study is an empirical investigation of this assumption. It is hypothesized that an organization's actual human resource programs affect employee perceptions of the organization's commitment to human resource efforts, which in tum affect general employee work attitudes. The results of a field survey of two autonomous organizations supports this hypothesis. Practi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
42
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 18 publications
6
42
0
Order By: Relevance
“…These results support the findings of Kinicki, Carson and Bohlander (1992), who determined that HRM activities have positive impacts on employee attitudes. Previous studies have proven that job satisfaction and employee retention have a strong relationship with work performance (Harter, Schmidt & Hayes, 2002).…”
Section: Retentionsupporting
confidence: 82%
“…These results support the findings of Kinicki, Carson and Bohlander (1992), who determined that HRM activities have positive impacts on employee attitudes. Previous studies have proven that job satisfaction and employee retention have a strong relationship with work performance (Harter, Schmidt & Hayes, 2002).…”
Section: Retentionsupporting
confidence: 82%
“…Meyer and Kirsten (2005) contend that, managing performance of employees forms an integral part of an organization and reflects how they manage their human capital. Along the same lines, several authors (Caldwell et al, 1990;Kinicki et al, 1992;Ostroff,1992) assert that the integrated HR and PM policies has significant influence on employee attitude and commitment and these in turn influence the performance of the organization. This is consistent with the findings of Berger and Berger (2011) who emphasized that, an effective performance management system provides for assessment of individual performance and developing them to create sets of competencies that the organization requires.…”
Section: Career Development and Employee Competenciesmentioning
confidence: 99%
“…Previous research indicated that human resources management practices and the insights of the employees influence organizational commitment (Chang, 2005;Kinicki et al, 1992). We can refer to the perceptions of the employees of an organization's commitment to them as "perceived organizational support" (Eisenberger et al, 1986), where HRM practices are claimed to have a significant and positive impact on organizational performance (Ramsay et al, 2000;Wood, 1999).…”
Section: Hrm Practices and Organizational Commitmentmentioning
confidence: 99%
“…Thus, a key function of human resources management practices is to stand-in a suitable psychological agreement (Rousseau & Greller, 1994), and employee's psychological agreement with their employer may be affected by explanations of their employer's human resources management practices. Kinicki et al (1992) suggested that employee insights of an organization's commitment to human resource efforts is affected by an organization's real human resources management programs, which in turn affect employees' work attitude. An employee's relationship with an organization is shaped by HRM actions such as recruiting, appraising performance, training and benefits administration through which employees come to understand the terms of their employment (Rousseau & Greller, 1994).…”
Section: Human Resource Management Practices Psychological Contractsmentioning
confidence: 99%
See 1 more Smart Citation